QTL mapping for leaf rust resistance in a recombinant inbred line population from the cross of wheat cultivars Zhongmai 578/Jimai 22 - Yue Zhang; Lei Li; Zaifeng Li; Yubing Tian; Fangping Yang; Shuanghe Cao; Xianchun Xia; Yongjing Ni; Zhonghu He; Yan Zhang; Yong Zhang; Jindong Liu (Phytopathology Research)
Abstract Leaf rust is a highly destructive disease that poses a significant threat to both the yield and quality of wheat. Identification of genetic loci can aid in enhancing leaf rust resistance in wheat breeding. In the present study, 262 recombinant inbred lines derived from a cross between Zhongmai 578 and Jimai 22 were used to map leaf rust resistance loci using the Wheat 50K single-nucleotide polymorphism (SNP) array across four environments. Four quantitative trait loci (QTL) on chromosomes 2B (2), 5B, and 7B were identified through composite interval mapping, designated QLr.caas-2B.1, QLr.caas-2B.2, QLr.caas-5B, and QLr.caas-7B, respectively, explaining 3.7%–19.6% of the phenotypic variances. The resistance alleles at QLr.caas-2B.1, QLr.caas-5B, and QLr.caas-7B originated from Zhongmai 578, while that at QLr.caas-2B.2 came from Jimai 22. Both QLr.caas-2B.2 and QLr.caas-5B overlapped with loci previously reported, whereas QLr.caas-2B.1 and QLr.caas-7B are likely to be new loci. Two kompetitive allele-specific PCR (KASP) markers, KASP-QLr.caas-2B.2 and KASP-QLr.caas-5B, were proven to be significantly associated with leaf rust resistance in a diverse panel of 119 wheat varieties mainly from China. Four candidate genes encoding a lectin-receptor kinase protein, F-box family protein, ankyrin repeat domain protein, and putative ABC transporter, respectively, were identified in genetic regions of the four QTL. These findings provide valuable QTL and breeding available KASP markers, facilitating the improvement of leaf rust resistance in wheat through marker-assisted breeding.